Advanced task scheduling algorithm for IoT Based FOG communication model - Mohammed, Zaber; Chowdhury, Riham; Rozario, Stanley Dip; Sakin, Sayed Bin Amirul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.